PRELIMINARY ANALYTICAL STUDY OF SAINDHAVADYA GHRUTA (International Journal of Ayurveda and Pharma Research, 2015)
Ghruta is considered best among the Snehas. Its usage is being highlighted by our Acharyas in the disorders of brain like Unmada, Apasmara etc. This study focuses on one such preparation Saindhayadya ghruta mentioned in Yogaratnaka Apasmara chikitsa. Literary review done through various sources like books, journals and internet revealed that, no studies have been carried out on this formulation yet. Hence an attempt was made to study Saindhayadya ghruta through qualitative and quantitative analysis of Physico-chemical parameters and to develop fingerprints of High-Performance Thin Layer chromatography study (HPTLC). HPTLC densitometric scan of chloroform extract of unsaponifiable matter of Saindhvadhya Ghruta showed 9 and 6 spots at 254nm and 366nm respectively. To interpret the results, there are no previous standard markers established for Saindhavadya ghruta. This analytical profile may help in the identification of Saindhavadya ghruta in future and to maintain the standard quality of the formulation.